2005
DOI: 10.17796/jcpd.28.2.n18275821658263v
|View full text |Cite
|
Sign up to set email alerts
|

Tongue scrapping as a means of reducing oral mutans streptococci

Abstract: Mutans streptococci (MS) are one of the most virulent cariogenic pathogens in the oral cavity. The effects of three oral hygiene techniques on salivary mutans streptococci levels were evaluated to see which mechanism would be most efficient in reducing salivary MS levels. Sixty patients, all in the permanent dentition, were selected and randomly distributed into three groups. Group I was asked to use a tongue scraper to brush the tongue once daily in the morning after normal tooth brushing routine. Group II wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
2
13
0
1
Order By: Relevance
“…Our data are in agreement with White and Armaleh (23) who compared the efficiency of tongue scraping, saturated saline rinse and Listerine strips in reducing salivary mutans streptococci levels. They found that all the treatment groups showed a significant reduction in colony counts from baseline to one or more post‐treatment periods.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data are in agreement with White and Armaleh (23) who compared the efficiency of tongue scraping, saturated saline rinse and Listerine strips in reducing salivary mutans streptococci levels. They found that all the treatment groups showed a significant reduction in colony counts from baseline to one or more post‐treatment periods.…”
Section: Discussionsupporting
confidence: 92%
“…They found that all the treatment groups showed a significant reduction in colony counts from baseline to one or more post‐treatment periods. Tongue scraping was found to be more effective than saturated saline rinse and Listerine strips in reducing colony counts (23). However, their study was carried out on adult subjects who practiced the oral hygiene measures only once daily for seven days.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicated that tongue-cleaning reduced the number of oral bacteria (Gilmore and Bhaskar, 1971, 1972, Yonezawa, et al, 2003 and odor (Yaegaki and Sanada, 1992). Tongue-cleaning using a tongue-brush reduced salivary mutans streptococci (White and Armaleh, 2004). In this study, 40 of the patients were classified according to number of salivary viable microorganisms, with the group yielding a high viable bacterial cell number showing a higher average score for TPI.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have shown that dorsum of the tongue is an important reservoir for mutans streptococci. 5 Further more, studies have also found a significant correlation between the prevalence of mutans streptococci in saliva and its prevalence on the dorsum of the tongue. 5 Mutans streptococci (MS) are one of the most virulent cariogenic pathogens in the oral cavity.…”
Section: Why Clean the Tongue?mentioning
confidence: 97%
“…5 Further more, studies have also found a significant correlation between the prevalence of mutans streptococci in saliva and its prevalence on the dorsum of the tongue. 5 Mutans streptococci (MS) are one of the most virulent cariogenic pathogens in the oral cavity. Toothbrushing alone is effective in reducing bacterial counts in the mouth, but not dramatically.…”
Section: Why Clean the Tongue?mentioning
confidence: 97%